Calcium and calcium isotope changes during carbon cycle perturbations at the end‐Permian. (21st January 2016) - Komar, N.; Zeebe, R. E.
Abstract: Negative carbon and calcium isotope excursions, as well as climate shifts, took place during the most severe mass extinction event in Earth's history, the end‐Permian (∼252 Ma). Investigating the connection between carbon and calcium cycles during transient carbon cycle perturbation events, such as the end‐Permian, may help resolve the intricacies between the coupled calcium‐carbon cycles, as well as provide a tool for constraining the causes of mass extinction. Here we identify the deficiencies of a simplified calcium model employed in several previous studies, and we demonstrate the importance of a fully coupled carbon cycle model when investigating the dynamics of carbon and calcium cycling. Simulations with a modified version of the Long‐term Ocean‐atmosphere‐Sediment CArbon cycle Reservoir model, which includes a fully coupled carbon‐calcium cycle, indicate that increased weathering rates and ocean acidification (potentially caused by Siberian Trap volcanism) are not capable of producing trends observed in the record, as previously claimed. Our model results suggest that combined effects of carbon input via Siberian Trap volcanism (12, 000 Pg C), the cessation of biological carbon export, and variable calcium isotope fractionation (due to a change in the seawater carbonate ion concentration) represents a more plausible scenario. This scenario successfully reconciles δ 13 C and δ 44 Ca trends observed in the sediment record, as well as the proposed warming of >6°C. Key Points: Fully coupled carbon cycle model needed when investigating carbon‐calcium cycling dynamics Increased weathering and ocean acidification not capable of producing trends observed in Ca record Halt of biological export, variable Ca isotope fractionation, and input of 12, 000 Pg C the most likely scenario